1999
DOI: 10.1080/016909699386293
|View full text |Cite
|
Sign up to set email alerts
|

Memory Limitations and Structural Forgetting: The Perception of Complex Ungrammatical Sentences as Grammatical

Abstract: Results from an English acceptability-rating experiment are presented which demonstrate that people nd doubly nested relative clause structures just as acceptable when only two verb phrases are included instead of the grammatically required three. Furthermore, the experiment shows that such sentences are acceptable only when the intermediate verb phrase is omitted. A number of speci c accounts of forgetting are considered. Two early proposed theories of this effect, the disappearing syntactic nodes hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
225
4
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(253 citation statements)
references
References 24 publications
(29 reference statements)
16
225
4
8
Order By: Relevance
“…This missing-verb effect ( [10]; figure 2) is likely related to real-time memory overload as the language system needs to keep track of too many unresolved dependencies [10]. Apparently, resolving three non-adjacent dependencies puts too much load on available memory.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…This missing-verb effect ( [10]; figure 2) is likely related to real-time memory overload as the language system needs to keep track of too many unresolved dependencies [10]. Apparently, resolving three non-adjacent dependencies puts too much load on available memory.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…An interesting demonstration comes from Gibson & Thomas [10], who investigated the role of memory limitations on processing sentences that contained three nested dependencies. They observed that speakers of English would rate the grammatical sentence in 1a no better that its ungrammatical counterpart in 1b, which is missing the middle verb phrase: -1a.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, which we call noisy-context surprisal, the processing cost of a word is the surprisal of the word given a noisy representation of the preceding context. We show that this model accounts for an outstanding puzzle in sentence comprehension, language-dependent structural forgetting effects (Gibson and Thomas, 1999;Vasishth et al, 2010;Frank et al, 2016), which are previously not well modeled by either expectation-based or memory-based approaches. Additionally, we show that this model derives and generalizes locality effects (Gibson, 1998;Demberg and Keller, 2008), a signature prediction of memory-based models.…”
mentioning
confidence: 99%
“…Another related theory is Early Immediate Constituents (EIC; Hawkins, 1994), which assigns a greater processing cost when there is an increase in the number of words that make up a syntactic constituent. The SPLT and DLT, in particular, have yielded a rich body of experimental research that provides strong support for the existence of distance effects in English (e.g., Gibson & Thomas, 1999;Grodner & Gibson, 2005;Warren & Gibson, 2005).…”
Section: Introductionmentioning
confidence: 99%